Exploitation Of Street-Having Children In Medan, North Sumatera Province - Effiati Juliana Hasibuan; Indra Muda; Waridah Pulungan; Mulia Siregar (Technium Social Sciences Journal, 2020)
Street beggar children are children who are actually excluded, marginalized and alienated from the treatment of affection because at a relatively early age already dealing with a harsh city environment. Street beggar children usually do activities on the streets such as, begging at the intersection of red lights, on the edge of a strategic road, at the location of the tax or market. The problem in this research is, how the Medan City Government’s efforts to deal with street begging children, what actions are given to those who commercialize street beggar children. To obtain data used in-depth interview research techniques, observation and documentation. While the data analysis mechanism is done by data reduction and data presentation. Based on the results of research that, efforts to deal with street beggars in the city of Medan have not been maximized. Seems like just a formality for an annual activity report. Likewise, the facilities and facilities for street begging children in the Punge Binjai Orphanage are still far from expectations. Even this building is owned by the North Sumatra Provincial Social Service while the Medan City Social Service is not available until October 2019. Actions for the exploiters of street beggar children are not available, only in the form of warnings, guidance from the Social Service. The personal data of the exploiters of street begging children, both individuals and groups, are known to the Medan City Social Service, but do not have the authority to make arrests. For the task of arrest has been submitted to the police, but strict action in the form of body detention has never been done